What limits the spread of two congeneric butterfly species after their reintroduction: quality or spatial arrangement of habitat - van Langevelde, F; Wynhoff, I (Animal conservation, 2009)
Population growth and spread of recently reintroduced species is crucial for the success of their reintroduction. We analysed what limits the spread of two congeneric butterfly species Maculinea teleius and Maculinea nausithous, over 10 years following their reintroduction. During this time, their distributions appeared to be limited to a few sites although it was thought that more suitable habitats were available. Thus, we question, does the quality or the spatial arrangement of their habitat limit their spread? Although adult individuals of both species can select high-quality plots, we show that selection of suitable plots in the area of reintroduction is spatially constrained. A low colonization probability of unoccupied distant plots of high quality was found for both species. The abandonment of occupied plots in Ma. teleius was also found to be dependent on the distance to occupied plots. We conclude that the spatial distribution of the two species during the 10 years following reintroduction was limited by the spatial arrangement of their habitat, rather than by the availability of high-quality plots. The spatial constraints in movement can explain observed source-sink structures when female butterflies deposit their eggs on low-quality plots. We conclude that although these species have very similar life histories, they require different approaches to their conservation due to subtle differences in adult habitat use and movement. Conservation of Ma. teleius should concentrate on improving local habitat quality, whereas conservation of Ma. nausithous is predicted to be more effective by creating a spatial network of suitable habitat plots, such as along road verges.